The Law’S Autonomy and a Practical Law-View. Preliminaries to Legal Discourse Analysis - Pichlak, Maciej (University of Wroclaw. Faculty of Law, Administration & Economics, 2014)
The paper elaborates basic foundations for a new methodological account of the autonomy of law. It argues that the problem of the law’s autonomy, however broadly discussed in the past, still awaits a fully plausible and comprehensive examination. The main attempt is made in three successive steps: first, existing analyses of the law’s autonomy are briefly recapitulated. Second, the main contemporary challenges in the field are pinpointed. These are: the increasing reflexivity of legal institutions, the growing (even if not explicitly indicated) relevance of the problem of the law’s autonomy in present-day jurisprudential debates, and some theoretical deficiencies of existing analyses of the problem under discussion; as to the last point, the existing analytical considerations should be complemented with more empirical, sociological insights. In the last, third step a research programme is proposed based on Sociological Discourse Analysis methodology. The main analytical tool used herein is the concept of law-view, which is put forward and explained in the study.
Keywords: autonomia prawa